New algorithms for macromolecular simulation - Leimkuhler, B. (Lecture notes in computational science and engineering, 2006)
Molecular simulation is a widely used tool in biology, chemistry, physics and engineering. This book contains a collection of articles by leading researchers who are developing new methods for molecular modelling and simulation. Topics addressed here include: multiscale formulations for biomolecular modelling, such as quantum-classical methods and advanced solvation techniques; protein folding methods and schemes for sampling complex landscapes; membrane simulations; free energy calculation; and techniques for improving ergodicity. The book is meant to be useful for practitioners in the simulation community and for those new to molecular simulation who require a broad introduction to the state of the art. Macromolecular models: from theories to effective algorithms -- Membrane protein simulations: modelling a complex environment -- Modeling and simulation based approaches for investigating allosteric regulation in enzymes -- Exploring the connection between synthetic and natural RNAs in genomes: a novel computational approach -- Learning to align sequences: a maximum-margin approach -- Minimization of complex molecular landscapes -- Overcoming energetic and time scale barriers using the potential energy surface -- The protein folding problem -- Dynamical and stochastic-dynamical foundations for macromolecular modelling -- Biomolecular sampling: algorithms, test molecules, and metrics -- Approach to thermal equilibrium in biomolecular simulation -- The targeted shadowing hybrid Monte Carlo (TSHMC) method -- The langevin equation for generalized coordinates -- Metastability and dominant eigenvalues of transfer operators -- computation of the free energy -- Free energy calculations in biological systems. How useful are they in practice? -- Numerical methods for calculating the potential of mean force -- Replica-exchange-based free-energy methods -- Fast electrostatics and enhanced solvation models -- Implicit solvent electrostatics in biomolecular simulation -- New distributed multipole metdhods for accurate electrostatics in large-scale Biomolecular simulations -- Quantum-chemical models for macromolecular simulation -- Towards fast and reliable quantum chemical modelling of macromolecules -- Quantum chemistry simulations of glycopeptide antibiotics -- Panel discussion.